Awareness and perception regarding female foeticide among adolescents in rural community of Nalgonda district, Telangana - J., Kishore Yadav; Ganapa, Praveena; Fernandes, Joanna P.; D., Sreeharshika; S., Ramesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Female foeticide is perhaps one of the worst forms of violence against women where a woman is denied her most basic and fundamental right i.e. “the right to life”. Exorbitant dowry demand is one of the main reasons for female infanticide and other reasons include belief that it is only the son who can perform the last rites, that lineage and inheritance runs through the male line, sons will look after parents in old age, men are bread winners etc. The present study was aimed to assess the awareness & perception regarding female foeticide among adolescents in rural community. Methods: A cross-sectional study was conducted among 200 school students with a pre-tested, semi structured questionnaire in order to assess the awareness & perception regarding female foeticide among adolescents. Data collected was analysed using SPSS software. Results: Majority (52.5%) of the study subjects were males. Majority (70%) of the subjects could define foeticide. Boys have better knowledge than girls regarding current sex ratio (21%), state position(20%) and district position(33.3%).The most common reasons for not preferring girl child were not carrying family name and burden to the family. Major source of information was social media. Conclusions: This study reveals that there is considerable scope for spreading awareness to youth about this social malady with medical implications. This will not only change the perception and behaviour of future generation, but motivated adolescents can also influence the families and communityation.